Introduction and Implementation of the Internet of Things for Students Vocational High School 1 Punggur Besar - Hirzen Hasfani; Uray Ristian; Hafiz Muhardi; Kasliono; Cucu Suhey; Tedy Rismawan; Ikhwan Ruslianto; Rahmi Hidayati; Syamsul Bahri; Dwi Marisa Midyanti; Irma Nirmala; Suhardi; Kartika Sari (Digital Innovation, 2026)
The training program “Introduction and Implementation of IoT” at Vocational High School(VHS) 1 Punggur Besar aims to enhance students’ understanding and practical skills in developing IoT-based systems. The training introduces key IoT concepts, components such as sensors, actuators, and microcontrollers, and how devices communicate via the internet. Through hands-on sessions, students create simple projects like temperature and humidity monitoring systems, smart lighting, and sensor-based notifications. This program helps students build technical competence in hardware assembly and IoT programming while fostering creativity and problem-solving abilities. As a result, students gain better readiness to face industrial demands that rely on digital technologies and are encouraged to innovate in applying IoT to real-world challenges.